Exploring the Nexus between Islamic Household Management Principles and Home-Based Women Enterprises in Northern Nigeria - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Dalhatu, Rabi Shehu; Abdullahi, Hashimu; Zaki, Salisu Abba (IDRIS Darulfunun Institute, 2025)
This study looks into how women-led home-based businesses in Northern Nigeria operate in regard to Islamic household management concepts. In particular, it looks at how female entrepreneurs incorporate important Islamic principles like ?adl (justice), i?tid?l/?isr?f avoidance (moderation), and barakah (blessing) into their household and microbusiness management. In many Northern Nigerian villages, women are increasingly working in small-scale jobs including food processing, crafts, and tailoring to help support their families. While Islamic teachings provide a thorough framework for striking a balance between economic endeavours and household responsibilities, little empirical study has examined how women who own micro, small, and medium-sized enterprises (MSMEs) really implement these concepts in their dual roles. In Bauchi, Gombe, and Kaduna States, a purposive sample of twenty women running home-based MSMEs in a variety of trades participated in a qualitative multiple-case research. Semi-structured interviews, participant observation, and the examination of personal and professional documents were used to gather data. To find trends in the distribution of profits, time management, resource allocation, and social duties, thematic analysis was used. The results show that women entrepreneurs' daily choices are greatly influenced by Islamic values. Participants established shared-storage practices in line with Islamic moderation, prioritized halal sourcing, and reduced waste through group purchases. Maintaining balance between work, religion, and childcare was made easier by planning work schedules around daily prayers. With a methodical allocation to home needs, business reinvestment, zakat responsibilities, and voluntary charity, profit distribution techniques also mirrored Islamic standards of fairness. The study comes to the conclusion that Islamic household management concepts offer a useful moral and practical framework that improves the long-term viability of women-owned businesses. In Northern Nigeria, strengthening these practices through women-focused support programs, faith-based business training, and community microfinance can further foster local economic development and family resilience.